The early Latin Church Fathers on Herod and the Infanticide - Mans, M. J. (Hervormde teologiese studies, 1997)
Since the views of the early Latin Church Fathers on Herod and the carnage at Bethlehem have been neglected by modem scholars, this study is an attempt to discover and interpret their opinions on the notorious king and this tragic event. Apparently, the main aim of the Latin Church Fathers was to present Herod's heinous deed in the worst possible light, and to exalt the Innocents to the ranks of the martyrs.